Food insecurity and nutritional biomarkers in relation to stature in Inuit children from Nunavik - Dallaire, Renée; Lucas, Michel; Ayotte, Pierre; Muckle, Gina; Dewailly, Éric; Jacobson, Joseph L.; Pirkle, Catherine; Jacobson, Sandra W. (Canadian Journal of Public Health, 2016)
OBJECTIVES: Inuit in Canada experience alarming levels of food insecurity, but nutritional and physiological consequences are poorly documented, especially in school-age children. The objective of this study was to assess the relation of food insecurity to iron deficiency and stature in school-aged Inuit children from Nunavik (Northern Quebec). METHODS: Food insecurity, iron deficiency, and stature were assessed in a cohort of children. Food insecurity was determined by interviewing the children’s mothers. Multiple logistic regression was used to evaluate the association of food insecurity to iron deficiency and short stature. We defined short stature as a height in the lowest tertile for age and sex, based on Canadian growth charts. The relation of food insecurity to height (cm) was analyzed with a general linear model. Statistical models controlled for age, sex, normal/overweight/obese status, prenatal lead exposure and postnatal polychlorinated biphenyls exposure. RESULTS: Half of the children (49.7%, n=145) were food insecure, while one third were iron depleted, 12.6% had anaemia, and 8.7% had irondeficiency anaemia. The multivariate odds ratio of anaemia was 1.82 (95% CI: 0.97, 3.42, p=0.06) for food-insecure children. Prevalence of short stature was 18.7%. Food-insecure children were an average of 2 cm shorter (95% CI: -0.48, -3.17) than food-secure children (p<0.01). CONCLUSION: In this population, food-insecure children have greater burdens of nutritional deficiencies and slower linear growth. Considering the high prevalence of food insecurity among Inuit children in Nunavik, nutritional deficiencies and adverse effects on development should be carefully monitored. OBJECTIFS : Les Inuits du Canada présentent des niveaux d’insécurité alimentaire alarmants dont les conséquences nutritionnelles et physiologiques sont méconnues, surtout chez les enfants d’âge scolaire. L’objectif de notre étude était d’évaluer la relation entre l’insécurité alimentaire, d’une part, et la carence en fer et la taille, ...